Diagnosing chronic rhinosinusitis: a comparative study between diagnostic nasal endoscopy and computed tomographic scan paranasal sinuses - Parmar, Dharmishtha H.; Maniyar, Hiten R.; Patel, Hetna A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: The term ‘rhinosinusitis’ refers to a heterogenous group of disorders characterized by inflammation of mucosa of the nose and paranasal sinuses. The National Institute of Allergy and Infectious Diseases (NIAID) have recently mentioned that 136 million people of India suffer from chronic rhino sinusitis. Methods: A total 50 patients with symptoms of rhinosinusitis were investigated with both diagnostic nasal endoscopy and CT scan paranasal sinuses and their findings were scored with particular scoring system and compared with each other. Results: Out of 50 patients, 90% patients were diagnosed on CT scan and 84% patients were diagnosed on nasal endoscopy. By considering CT scan as accurate procedure and correlating nasal endoscopy with CT scan, sensitivity was 88.88%, specificity was 60%, positive predictive value was 95.23%, negative predictive value was 37.5%, and p value was 0.004671, which was significant at p<0.05, indicates that CT paranasal sinuses is more accurate than diagnostic nasal endoscopy in diagnosing chronic rhinosinusitis. Conclusions: Both diagnostic nasal endoscopy and CT paranasal sinuses are important pre-operative evaluation tools in detecting pathology and both are complementary to each other. But CT paranasal sinuses are more convenient than endoscopy according to this study.